Efektivitas Kombinasi Zeolit dan Batu Apung dalam Menurunkan Konsentrasi Besi (Fe) pada Air Tanah: Studi Kasus di Pidada, Kecamatan Panjang, Bandar Lampung - Dalimunthe, Sahriwani; Fajar, Mutiara; Noor Azizah, Rifka (Dampak, 2024)
Water is a very important component for all life on earth. Iron is a heavy metal, and levels can be dangerous if they exceed threshold levels. Preliminary tests show that Fe in well water is 1.66 mg/l. This study aims to analyze the effectiveness of removal of iron (Fe) contained in well water using a combination of zeolite – pumice adsorbent media. One method that can be used to set aside iron (Fe) parameters in well water is the adsorption method. The adsorption process was carried out continuously with downflow for 150 minutes with sampling every 30 minutes for analysis with a Hach DR 1900 series spectrophotometer. Based on the results of the FTIR characterization analysis of zeolite adsorbents it was indicated that the functional groups were O–H hydroxy stretching vibrations, O-H bending vibrations, stretching vibrations. asymmetric Si-O-Si or Al-O-Al and symmetrical stretching vibration Si-O-Si or Al-O-Al. While the pumice adsorbent before and after being activated, there was a shift in wave numbers with the same functional groups, namely the O-H, C=O, Si-O and Al/Si-O bond groups. Of the five treatments, it is known that treatment V (ZEO30-AP70) is the most effective treatment in reducing Fe levels in well water with a removal efficiency of 98% in the 90th minute and the suitable isotherm model is the Langmuir isotherm with a maximum adsorption capacity of 0, 000739809 mg/g. Keywords: Well water, adsorption, zeolite, pumice